FINANCIAL MANAGEMENT IN VILLAGE AND AGRICULTURAL DEVELOPMENT - Devi, Luh Putu Parendra Indra; Suamba, I Ketut; Arisena, Gede Mekse Korri (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The existence of SiLPA (Excess Budget Calculation) in village financial management is an abstract thing that can indicate a surplus village financial condition but also indicates that the absorption of budget could be more optimal. Being the region in Bali Province with the lowest SiLPA ratio in 2018 and 2019, Tabanan Regency has demonstrated budget management capabilities despite the large number of villages in its area. The impact of village financial management also affects the development of village agriculture, which is the primary employment in Tabanan, the title of Bali's main rice barn. This study examined the relationship and influence of village revenue and expenditure on SiLPA and the causes of SiLPA in Tabanan Regency. This research is confirmatory research with GSCA analysis that used to analyze the relationship and influence of village income and expenditure on SiLPA in Tabanan Regency. Meanwhile, qualitative descriptive analysis is used to examine the causes of SiLPA in Tabanan Regency.The results show that P1, P3, and B5 matter positively affect S. Meanwhile, P2 and B1 have a negative effect on S. The causes of SiLPA are dominated by force majeure and planning.